Open internet access to CATV networks: experiences from the EU - Peggy Valcke; Liyang Hou; David Stevens (International Telecommunications Society (ITS), 2011)
Broadband over CATV networks is flourishing in the EU and in some Member States it even has already made significant impact on the retail broadband market. Our article aims to provide an overview of the regulatory treatment of broadband over CATV under the electronic communications regulatory framework. For this purpose, we carry out a survey of the different approaches within the 27 EU Member States. Based on the comments of the European Commission within the EU consultation procedure, our observation is that open Internet access obligations upon CATV operators remains limited.
Keywords: 330; access regulation; CATV; broadband